Violent delinquency in America the determinants of carrying firearms among juveniles: a theoretical comparative analysis - Wallace, Douglas Scott Larson (Kansas State University, 2009)
This study examined three of the prominent theories of juvenile delinquency to determine principle juvenile firearm carrying behaviors. The theories investigated were Differential Association/Social Learning, Social Control, and Anomie/Strain. The data set used for this research was the “National Survey of Weapons-Related Experiences, Behaviors, and Concerns of High School Youth in the United States, 1996” from the Inter-University Consortium for Political and Social Research at the University of Michigan. This national-level survey of youth was conducted by Joseph F. Sheley and James D. Wright to assemble detailed behavioral and attitudinal data concerning weapons and violence, and was completed by 733 10th and 11th grade male high school students. Comparison logistic regression model analyses were utilized to examine the study’s hypotheses. Findings indicated that juvenile firearms carrying is most influenced by delinquent peers, delinquent friends, and gang membership within the theoretical framework of Differential Association/Social Learning. Social Control Theory has the least explanatory power, while the analysis of Anomie/Strain suggests that vicarious strains (those strains experienced by people close to the juvenile) have even more influence on juvenile firearms carrying than experienced strain. Theoretical integration is recommended for future research attempting to provide greater explanatory and predictive power for serious forms of delinquency like juvenile firearms carrying.
Keywords: Juvenile delinquency; Strain theory; Social learning; Social control; Firearms; Gun violence; Sociology, Criminology and Penology (0627); Sociology, General (0626); Sociology, Theory and Methods (0344)